Niewerbalne elementy komunikacji w sytuacjach oficjalnych. Analiza debaty z udziałem liderów politycznych - Karaśkiewicz, Agata (Investigationes Linguisticae, 2010)
The primary goal of this article is to examine politicians` nonverbal behaviors observed in the official situations, such as televised debate. Good communication is the foundation of successful relationships, both personally and professionally. But we communicate with much more than words. In fact, when we interact with others, we continuously give and receive countless wordless signals. This article aims at showing various nonverbal signals displayed by dominant polish political figures – leader of The Civic Platform Donald Tusk and The Law and Justice Jarosław Kaczynski. To set this idea a televised debate, which took place on September 12, 2007 - before the country`s upcoming general election, is analyzed in detail. The author also looks how the behavior style is determined by the official character of the communication. In this context nonverbal signals observed in official face–to-face conversation between two interlocutors are discussed and may be the first step to further research of general tendency in nonverbal behavior.